Towards the Development of Long Circulating Phosphatidylserine (PS)- and Phosphatidylglycerol (PG)-Enriched Anti-Inflammatory Liposomes: Is PEGylation Effective? - Miriam E. Klein; Max Rieckmann; Daniel Sedding; Gerd Hause; Annette Meister; Karsten Mäder; Henrike Lucas (Pharmaceutics, 2021)
The anionic phospholipids (PLs) phosphatidylserine (PS) and phosphatidylglycerol (PG) are endogenous phospholipids with anti-inflammatory and immunomodulatory activity. A potential clinical use requires well-defined systems and for several applications, a long circulation time is desirable. Therefore, we aimed the development of long circulating liposomes with intrinsic anti-inflammatory activity. Hence, PS- and PG-enriched liposomes were produced, whilst phosphatidylcholine (PC) liposomes served as control. Liposomes were either formulated as conventional or PEGylated formulations. They had diameters below 150 nm, narrow size distributions and composition-dependent surface charges. Pharmacokinetics were assessed non-invasively via in vivo fluorescence imaging (FI) and ex vivo in excised organs over 2 days. PC liposomes, conventionally formulated, were rapidly cleared from the circulation, while PEGylation resulted in prolongation of liposome circulation robustly distributing among most organs. In contrast, PS and PG liposomes, both as conventional or PEGylated formulations, were rapidly cleared. Non-PEGylated PS and PG liposomes did accumulate almost exclusively in the liver. In contrast, PEGylated PS and PG liposomes were observed mainly in liver and spleen. In summary, PEGylation of PS and PG liposomes was not effective to prolong the circulation time but caused a higher uptake in the spleen.